Extension of the Application Range of Multipolar Bonded Ring Magnets by Thermosets in Comparison to Thermoplastics - Rösel, Uta; Drummer, Dietmar (Magnetism, 2023)
To expand the range of applications of multipolar bonded magnets based on a thermoplastic matrix, the chemical and thermal resistance has to be increased and the reduced orientation in the rapid solidified surface layer has to be overcome. To meet these requirements, the matrix of multipolar bonded magnets can be based on thermosets. This paper investigates in the magnetic properties, especially in the orientation of hard magnetic fillers, the pole accuracy and the mechanical properties of multipolar bonded ring magnets based on the hard magnetic filler strontium-ferrite-oxide and compares the possibilities of thermoplastic (polyamide)- and thermoset (epoxy resin, phenolic resin)-based matrices. It was shown that the magnetic potential of the thermoset-based material can only be fully used with further magnetization. However, the magnetic properties can be increased using thermoset-based compounds compared to thermoplastics in multipolar bonded ring magnets. Further, a model of the orientation and pole accuracy is found in terms of thermoset-based multipolar magnets. In addition, the change of the mechanical properties due to the different matrix systems was shown, with an increase in E-Modulus, Et, and a reduction in tensile strength, σm, and elongation at break, εm, in terms of thermosets compared to thermoplastics.<br
Keywords: hard magnetic filler; highly filled thermosets; polymer-bonded magnets; multipolar magnets